We have to prove that (sin x)^4 + (cos x)^4 + (sin 2x)^2/2 = 1

(sin x)^4 + (cos x)^4 + (sin 2x)^2/2

=> (sin x)^4 + (cos x)^4 + (2*sin x * cos x)^2/2

=> (sin x)^4 + (cos x)^4 + 4*(sin x)^2*(cos x)^2/2

=> (sin x)^4 + (cos...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to prove that (sin x)^4 + (cos x)^4 + (sin 2x)^2/2 = 1

(sin x)^4 + (cos x)^4 + (sin 2x)^2/2

=> (sin x)^4 + (cos x)^4 + (2*sin x * cos x)^2/2

=> (sin x)^4 + (cos x)^4 + 4*(sin x)^2*(cos x)^2/2

=> (sin x)^4 + (cos x)^4 + 2*(sin x)^2*(cos x)^2

=> [(sin x)^2 + (cos x)^2]^2

=> 1^2

=> 1

**This proves that (sin x)^4 + (cos x)^4 + (sin 2x)^2/2 = 1**